AN ANALYSIS ON THE EFFECTIVENESS OF ACTIVE LEARNING ACTIVITIES FOR STUDENTS OF DIFFERENT LEARNING STYLES IN PETROLEUM ECONOMICS - Kanesan, Dinesh (Proceedings of the International Conference on Education, 2019)
Determining the most effective pedagogical technique to be used during teaching and learning activities has been one of the most challenging task faced by educators. Unless until educators understand how each student learns best, they may not be able to help the students to learn better. Although one can have a mix of learning styles, there would be one particular dominant learning style. However, one can also develop their ability and learn in their less dominant style of learning. In this research, the learning styles of the students taking the Petroleum Economics Module at Universiti Teknologi PETRONAS was assessed using the Index of Learning Styles (ILS) tool developed by Felder and Solomon. In addition, the effectiveness of conducting lessons according to the identified learning styles was also analyzed. From the ILS tool outcome, the students were further grouped according to their learning preference in the active or reflective domain. Out of 80 students, 59% have been identified to be active learners and the remaining 41% are reflective learners. Four different active learning activities namely focused listing, brain storming, pair testing and closure review pairs were implemented during lectures for four consecutive weeks throughout the semester to study the effectiveness of active learning activities among active and reflective learners. Based on the analysis conducted from the coursework and final exam marks, it was found that there is no significant evidence that active learners benefit more from active learning activities compared to reflective learners. In addition, the results suggest that active learning promotes short term memory retention for all students irrespective of learning style preference.